Strategi untuk Membantu Meningkatkan Perencanaan Karier Siswa di Era Revolusi Industri 4.0 - Parid Rilo Pambudi; Muslihati Muslihati; Blasius Boli Lasan (JKI (Jurnal Konseling Indonesia), 2019)
The development of Science and Technology is very rapid, of course, impact on the challenges and global competition faced by every country, one of which is Indonesia. Therefore quality human resources are needed. Quality human resources are formed through education five main characters are enhanced and must be possessed by students in Strengthening Character Education. These characters must be possessed by students of the industrial revolution era 4.0 to be able to enter the workforce and be ready to compete with other countries. Every student certainly wants a brilliant career, and that career is realized with an effort and planned carefully. All efforts undertaken by the counselor in helping students to plan further studies and their careers will not succeed without the right strategy. The strategy to improve students' career planning skills in the industrial revolution era 4.0 is Four C’s, which is a guidance-based strategy. Four C’s is a strategy to improve the ability to think at a higher level (critical thinking, creativity, collaboration, and communication).